Tradition, Social Values, and Fiqh of Civilization: Examining the Nyadran Ritual in Nganjuk, East Java, Indonesia - Hasan, Nor; Taufiq, Muhammad; Hannan, Abd.; Ghafiri Enhas, Muhammad Iqbal (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2023)
This research focuses on examining the Nyadran ritual in Sono Ageng Village, Nganjuk Regency, approached through the relationship between tradition, social norms, and fiqh of civilization. The study used a qualitative approach with phenomenology as a method, utilizing John F. Haught's theory on the relationship between religion and culture, and both primary and secondary data. This study has three findings: First, Nyadran is an annual tradition containing the meaning of slametan, prayers, means to strengthen social relations, and respect for ancestors or forefathers who have greatly contributed to establishing the Sono Ageng Village. Second, although Nyadran was initially known to the public as a local tradition, subsequent developments reveal that Nyadran underwent a process of acculturation with the values and teachings of the Islamic religion. The relationship between religion and culture in the Nyadran tradition is formed through a process of contact and confirmation. Third, from a Fiqh of Civilization perspective, the values contained in Nyadran includes gratitude for Allah's blessings, prayers for ancestors, a place for friendship, and a true transformation of social values in line with the visions of Fiqh of civilization. The implication of this study is the maintaining traditions and social harmony within the paradigm of Fiqh of Civilization to create an attitude of tolerance and moderation in the life of a pluralistic society.